Outcomes in patients with cardiac masses: the underestimated burden of pseudotumours. (25th November 2020) - Paolisso, P; Foa', A; D'Angelo, E.C; Saturi, G; Bergamaschi, L; Toniolo, S; Magnani, I; Bartoli, L; Angeli, F; Donati, F; Stefanizzi, A; Rinaldi, A; et al.
Abstract: Background: Cardiac masses (CMs) include benign and malignant formations. So far, clinical presentation and prognosis have been reported only in small series without discriminating between subtypes. We investigated the clinical presentation and long-term prognosis of patients with cardiac masses stratifying our results according to the lesions' nature. Methods: We enrolled all consecutive patients admitted to our Institution between 1999 and 2018 with imaging evidence of CMs. Definitive diagnosis was achieved by histologic examination or by radiological evidence of thrombotic resolution after anticoagulant treatment. The study population was classified as benign or malignant and subsequently into 4 subtypes: pseudo-tumours, primary benign tumours, primary malignant tumours and secondary tumours. Cardiovascular and non-cardiovascular mortality was described. Results: We identified 172 patients with CMs, 125 benign and 47 malignant. Benign lesions were often incidentally diagnosed in the left heart chambers whereas malignancies were usually detected in the pericardium and right sections, resulting in more advanced symptoms. Over time – median follow-up of 48 months - survival of patients with benign formations was three-fold greater than patients with malignancies (p<0.001) with no differences in cardiovascular mortality. Patients with pseudo-tumours showed a significantly lower survival than primary benign tumours (p=0.018) while no difference was found within the malignant stratum between primary and secondary neoplasms. Conclusions: CMs are a heterogeneous entity where advanced symptoms and a pericardial involvement suggest malignant forms, which exhibit a poor outcome. Among patients with benign lesions, pseudo-tumours were associated with reduced survival, supposedly as a consequence of the different underlying conditions. Funding Acknowledgement: Type of funding source: None